Dieting habits as a crucial factor for maintaing health in student population - Djordjevic-Pesic, Jasmina; Pešić, Vladan; Damnjanović, Goran (PONS - medicinski časopis, 2018)
Abstract Food habits influence different aspects of health among which are a subjective estimation of health, other life habits (such as physical activities), functional status, but also of health care, where inadequate diet represents a significant risk factor for the formation of numerous, various health disorders. It is estimated that around 31% children in the world under 5 is malnourished while mortality caused by illness, hunger or malnutrition makes even 50% of overall mortality in children. Basic aims of this research are to examine the dieting characteristics of pupils and students and to examine the differences in diets of pupils and students comparing to defined demographic and socio economical features of the examined. A cross-section study has been done on the sample of 480 pupils and students in Nis. The research in the field was performed between 20th November and 2nd December in 2014. ( special days for certain groups of subjects). As previously mentioned a statistical package computing program Statistical Package for Social Sciences (SPSS for Windows rel. 13.0). was used.The analysis shows that men have breakfast more rarely than women. The results are equal to the question if they never have breakfast. Unlike the previous results, men have lunch more often than women and the answers to the question if they have an afternoon snack are similar.The difference is more apparent when it comes to afternoon snacks, men have lunch more often which is the same for the habit of having dinner or supper. A specially interesting question was the one whether subjects think about their health when they choose what to eat. The most frequent answer was that they consider it sometimes, a little less than a half or 45.2%,  every third subject or 29.0% consider it often,  and only every sixth does it always (16.3%).Key words: Dieting habits; subjective estimation of health; malnutrition; overweight in children and youth; student population.